Zinc effects of maize and common bean grain yield and zinc use efficiency in Siaya County, Kenya - Mutambu, Dominic Mwanzia (2023)
Soil zinc deficiency is a modern-day challenge in the global food production systems, lowering crop yields and yield quality. Research shows that crop yields and nutritional quality can be restored, and human health burden reversed by agronomic bio-fortification of zinc in staple crops. As a result, this study was designed to: i) determine the effects of nano-particulate zinc oxide, zinc sulphate, and chelated zinc on maize and common bean yields; ii) establish the effects of nano-particulate zinc oxide, zinc sulphate and chelated zinc on grain nutrient accumulation in maize and common bean, and iii) evaluate the effects of nano-particulate zinc oxide, zinc sulphate and chelated zinc on agronomic efficiency in maize and common bean in Siaya County. The experiment was laid in a randomized complete block design constituting twelve treatments in 7 m by 4.5 m plots replicated four times during 2020 short rains and 2021 short and long rains. All treatments received 90 N, 60 P and 60 K kg ha-1. The treatments were NPK only (control), NPK + nano-particulate ZnO (10, 15 and 20 kg Zn ha-1), NPK + zinc sulphate hepta-hydrate (11.4, 17 and 20 kg Zn ha-1) each as one-time and split application, NPK + nano-particulate zinc oxide foliar (2 g litre-1) and NPK + chelated zinc foliar (1 millilitre litre-1). Before the experiment was laid out soil samples were collected and analyzed for plant available Zn, Olsen P and pH. Crops were harvested at physiological maturity; grain samples were taken, and yields determined at 12.5% moisture content. A sub-sample of the grain was used to determine the nutritional quality following standard procedures. The pre-planting soil was moderately acidic (pH = 5.0), zinc (Zn = 0.66 ppm), and phosphorous (P = 3.60 ppm) deficient. The data were analysed by the analysis of variance and means separated by Fisher’s LSD at 95% confidence interval. Over the three seasons, maize grain yield ranged from 4.2 to 6.4 t ha-1 while bean grain yield was 0.315 to 1.68 t ha-1. Zinc application either achieved the same or increased maize grain yields marginally (8.2%) above the control. Zinc fertilizers did not significantly increase the maize and common bean grain nitrogen, phosphorus, potassium, sulphur, protein, boron, copper, iron, and manganese. Grain zinc concentrations ranged from 18.8 to 23.6 mg kg-1. Use of nano-particulate zinc oxide (soil), zinc sulphate, nano-particulate zinc oxide (foliar) and chelated zinc increased the maize grain Zn by 7.4, 15.8, 17.0 and 25.5%, respectively. Common bean grain Zn ranged from 23.03 to 30.3 mg kg-1 and was significantly increased (p<.001) in all Zn treatments, by up to 19.3% by the application of zinc, above control. Foliar nano-particulate ZnO significantly (p<.001) increased the zinc agronomic efficiency by up to 445 and 198 kg grain kg Zn-1 in maize and bean, respectively. Zinc application did not increase maize and common bean grain yield but improved the grain nutritional quality. Use of zinc in maize and common bean production systems with aim of improving nutritional value is thus recommended.